Time, Magic and Danse Macabre — the Metaphors of the Death in Susanna Clarke’s Mrs Mabb - Żebrowski, Mateusz (Wzniosłość i makabra w literackich obrazach śmierci, 2014)
The article refers a metaphor of symbolic death in Susanna Clarke’s short story Mrs Mabb: time,magic, danse macabre. All of them are ingrained in an European culture, especially in ancient Celticculture, but also in Anglo-Saxon and ancient Greece culture. The references to the “samhain” festival,danse macabre, folklore, Anglo-Saxon and Greece mythologies lead to the conclusion that Mrs Mabb isthe short story, which links a lots of motives to exalt a women position in culture.